PEMBENTUKAN KEIMANAN MASYARAKAT ANALISIS SEJARAH AYAT-AYAT MAKKIYAH - Syahrini Harahap (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
Geographically the Alquran was revealed in twu places, namely in Mekkah and Madinah. Makkiyah is the term form the name of the verses of the Alquran that descended in the city of Mekkah or before the prophet migrated, while the verses that came down in Madina are called Madaniyah. The division of the group of Alquran verses is solely done by Allah or Rasulullah, but divison of this group is a classification of the results of the ijtihad scholars. The purpose of the Makkiyah verses was to the disbelievers who were in the city of Mekkah, which served as a means to change their beliefs and build success. The purpose of writing this article is to find out the history of the emergence society using the historical method with a historical approach to the relevatiof of Makkiyah verses.